2017
DOI: 10.1590/abd1806-4841.20175277
|View full text |Cite
|
Sign up to set email alerts
|

Florid cemento-osseous dysplasia and peripheral giant cell granuloma in a patient with neurofibromatosis 1

Abstract: We report a 35-year-old mulatto female patient with neurofibromatosis Type 1 who presented with facial asymmetry. The patient had two lesions: florid cemento-osseous dysplasia associated with peripheral giant cell granuloma. She was referred for surgical treatment of the peripheral giant cell granuloma and the florid cemento-osseous dysplasia was treated conservatively by a multidisciplinary team. So far, no changes have been observed in the patient's clinical status. We observed no recurrence of peripheral gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Their case fulfilled the diagnostic criteria for NF1 who had florid cemento-osseous dysplasia associated with PGCG unlike our case with no medical history. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their case fulfilled the diagnostic criteria for NF1 who had florid cemento-osseous dysplasia associated with PGCG unlike our case with no medical history. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Their case fulfilled the diagnostic criteria for NF1 who had florid cemento-osseous dysplasia associated with PGCG unlike our case with no medical history. 10 Ramesh et al reported a case of 57 year old female with a hybrid lesion that showed both features of PGCG and POFs in maxilla. Alveolar bone was not involved by the lesion and no calcified bone or cementum was present.…”
Section: Discussionmentioning
confidence: 99%